Taxation and accountability in sub-Saharan Africa - Roel Dom; Oliver Morrissey; Abrams Mbu Enow Tagem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Taxation can contribute to state-building through a tax bargain in which taxpayers are willing to increase compliance in return for improved government accountability. There is limited evidence for this in sub-Saharan Africa where it is argued that the fiscal state is weak, with low tax revenues and governments that are not accountable. However, since the early 2000s, sub-Saharan African countries on average have increased tax/gross domestic product ratios significantly and there have also been increases in measures of accountability. Has the increase in taxation promoted improved accountability? This paper analyses data for up to 47 African countries from 1980 to 2019 and shows a robust positive correlation between tax revenue and accountability. Instrumental variable estimation provides support for a causal interpretation. The effect of taxation is only observed for vertical accountability (capturing the quality of elections and party competition), and not for other measures of accountability that capture the role of civil society or the judiciary, consistent with the emergence of a tax bargain. Furthermore, we show that the tax effect is one of the significant determinants of vertical accountability.
Keywords: H20; O55; 330; tax revenue; vertical accountability; tax bargain; sub-Saharan Africa